2008
DOI: 10.1111/j.1748-0361.2008.00163.x
|View full text |Cite
|
Sign up to set email alerts
|

The Methamphetamine Home: Psychological Impact on Preschoolers in Rural Tennessee

Abstract: These findings, if replicated, point to the need for mental health screening when a child is removed from a methamphetamine-producing home.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 13 publications
1
23
0
Order By: Relevance
“…Children from homes with a history of parental drug abuse or from a home with domestic violence were 3-3.5 times more likely to test positive to illicit drugs in urine or hair (137). When evaluated, children in methamphetamine homes showed higher levels of aggression than others where it is suggested that there is the need to assess the mental health of children removed from methamphetamine homes (112,116). It is suggested that the combination/accumulation of multiple risk factors have a greater negative impact on psychological development (71) than the individual factors alone.…”
Section: Confounding Factors For Evaluating Chronic Effects Of Exposurementioning
confidence: 99%
See 2 more Smart Citations
“…Children from homes with a history of parental drug abuse or from a home with domestic violence were 3-3.5 times more likely to test positive to illicit drugs in urine or hair (137). When evaluated, children in methamphetamine homes showed higher levels of aggression than others where it is suggested that there is the need to assess the mental health of children removed from methamphetamine homes (112,116). It is suggested that the combination/accumulation of multiple risk factors have a greater negative impact on psychological development (71) than the individual factors alone.…”
Section: Confounding Factors For Evaluating Chronic Effects Of Exposurementioning
confidence: 99%
“…Children removed from homes where methamphetamine has been manufactured (112)(113)(114)(115)(116) have been reported to display a range of behavioural issues including academic difficulties (12), developmental delay (78), a higher incidence and risk of externalising (acting out) problems (112)(113)(114)(115)(116), aggressive behaviour (112-116), post-traumatic or dissociative symptoms (114,115) and internalising problems (115). In addition children in environments where methamphetamine, and other drugs or abuse, are used or manufactured can also be exposed to a wider range of other chemicals, neglect, criminal behaviour, abuse (emotional, physical and sexual) that place these children at risk of developmental, behavioural and other mental health problems (114,115,(117)(118)(119)(120).…”
Section: Chronic Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…20,21 Our findings are consistent with others that have found behavior problems related to caregiver psychological symptoms 20,24 and poor-quality homes related to increased attention problems, aggression, and ADHD problems. 26,44 As the only cohort study of its kind, 1 limitation of the study is that our findings may not generalize to all populations of women who use MA during pregnancy. Furthermore, the sample was recruited at delivery, which may potentially affect recall of early pregnancy drug use.…”
Section: Discussionmentioning
confidence: 99%
“…Heavy use of methamphetamine and third-trimester use have been associated with increased neonatal physiological stress, increased lethargy, lower arousal, central nervous system irritability, and poor quality of movement (LaGasse et al, 2011;Smith et al, 2008). A few studies have reported high levels of posttraumatic stress disorder as well as externalizing and internalizing behaviors among preschool and school-age children of methamphetamine users (Asanbe et al, 2008;Ostler et al, 2007Ostler et al, , 2010.…”
mentioning
confidence: 99%